2019
DOI: 10.3390/w11101982
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change Scenarios on Non-Point Source Pollution in the Saemangeum Watershed, South Korea

Abstract: Non-point source (NPS) pollution is a primary cause of water pollution in the Saemangeum watershed in South Korea. The changes in NPS pollutant loads in the Saemangeum watershed for an 81-year period (2019–2099) were simulated and analyzed by applying the soil and water assessment tool. Six climate model (BCC-CSM1–1, CanESM2, GFDL-ESM2G, HadGEM2-CC, INM-CM4, and MIROC-ESM) outputs using representative concentration pathway (RCP) scenarios (RCP 4.5 and RCP 8.5) were obtained from the South Korean Asia-Pacific E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…Overall, the dominant feature detected was the widespread precipitation, maximum, and minimum temperature increase in the 21st century in the Jeonju station area. This result agreed with the previous study by Li and Kim et al [47], which reported the gradual increases of 70.9 to 233.8 mm and 1.7 to 5.7 • C in annual precipitation and temperature, respectively, for two periods (2019-2059) and (2060-2099) under RCP 4.5 and RCP 8.5 climate change scenarios…”
Section: Future Change In Precipitation Maximum and Minimum Temperaturesupporting
confidence: 93%
“…Overall, the dominant feature detected was the widespread precipitation, maximum, and minimum temperature increase in the 21st century in the Jeonju station area. This result agreed with the previous study by Li and Kim et al [47], which reported the gradual increases of 70.9 to 233.8 mm and 1.7 to 5.7 • C in annual precipitation and temperature, respectively, for two periods (2019-2059) and (2060-2099) under RCP 4.5 and RCP 8.5 climate change scenarios…”
Section: Future Change In Precipitation Maximum and Minimum Temperaturesupporting
confidence: 93%
“…So, the water volume is increased as water surface elevation increasing. These results are similar to those found in the previous researches (Jeong et al, 2018a;Li & Kim, 2019;Oda et al, 2019). Second, the water quality results from SCHISM-CoSiNE model including dissolved oxygen (DO), concentration of nitrate (NO 3 ) and concentration of phosphate (PO 4 ) are analyzed as the designated water surface elevations are varied at each regions of interest (see Figure 9).…”
Section: Resultssupporting
confidence: 93%
“…Before construction, the tidal range in the study area was up to 6 m; after construction, it is less than 1 m, even when the sluice gates are fully open [24,25]. The mean monthly air temperatures range from −0.4 • C (January) to 25.7 • C (August), and the mean annual precipitation is 1204 mm; precipitation mainly occurs during summer (June to September), which accounts for more than 65% of the total annual precipitation [26].…”
Section: Site Descriptionmentioning
confidence: 93%